Sistem Informasi Penjualan Label Printing pada PT. Citrajaya Labelindo - Eni Pudjiarti; Muhammad Tabrani (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
In this day and age, it takes a sound system to increase sales. The increase or development of sales is the goal of each company. There's a lot to do to increase sales, including a good marketing strategy. It is necessary for a medium to publish information, whether information about the company or goods to be sold. One of the media that can use is the internet. Companies can use the internet as a tool to publish various information or can make sales online or called E-Commerce. With e-commerce information or deals can be accessed wherever and whenever customers need. E-Commerce is one of the technologies applied within PT. Citrajaya Labelindo. Based on the description above, the author tried to create a design label printing sales website that aims to promote and provide information about the product, product price and product details quickly and updated. The use of the website expected to expand the marketing reach of the product without being limited by space and time, so as to increase sales. The website-based sales system was developed using waterfall development methods, with the PHP programming language and database used being MySQL.